An Overview of the CRoME Lab's MedSMA℞T Families Intervention for Promoting Opioid Medication Safety among Adolescents and Parents - Olufunmilola Abraham; Tyler McCarthy (University of Minnesota Libraries Publishing, 2023)
As the opioid epidemic unrelentingly places profound weight on pharmacists, youth, parents, and the nation at large, innovative interventions are critical to prevent potential misuse and untimely death. Adolescents are especially vulnerable to misuse behaviors due to knowledge, attitudinal, and social influences. To best resonate with adolescents, appropriate tools and technologies must be developed and deployed. Few educational tools are more ubiquitous to adolescents than video games. Video games, specifically serious games, have the potential to connect with adolescents and impart critical knowledge related to opioid safety. Engaging youth, parents, and pharmacists in the design, refinement, and evaluation of a serious game is novel and necessary for building a robust, efficacious game. This commentary describes the conceptualization, inception, development, and evaluation of a novel opioid medication safety intervention, MedSMA℞T Families. This two-part intervention is comprised of an adolescent-tailored serious game entitled MedSMA℞T: Adventures in PharmaCity, and a family-focused tool named the personalized Family Medication Safety Plan. This intervention is the first theory-based, family-focused opioid medication safety toolkit co-designed by an interdisciplinary team of researchers, game developers, behavioral health scientists, pharmacists, student pharmacists, addiction medicine physician, adolescent health physician, parents, and teens. Responses from key stakeholders (pharmacists, parents, and teens) have demonstrated positive attitudes and impressions towards both components of the MedSMA℞T Families intervention. Empirical evidence of efficacy from two separate studies denotes improvement in key concepts related to safe behavior in adolescents. Findings to date support the widespread use, implementation, and dissemination of this efficacious intervention to supporting safe opioid prescription practices in families with adolescents. In this paper, we outline and summarize our process of intervention development and use of longitudinal data to validate each step of our process. Future directions include mobile compatibility, refinement based on key stakeholder feedback, and dissemination in various clinical settings where opioid medications are prescribed and dispensed such as emergency departments, pharmacies, hospitals, and clinics.